Speech communication for the classroom teacher - Cooper, Pamela J (Gorsuch Scarisbrick, 1984)
The book provides prospective and in-sevice teachers in all subject matter areas experiences in analizing, developing, and facilitating their own and their students' communication behaviors. It is designed to be both theoretical and pragmatic, attempting to provide teachers with both the rationale for the use of certain communication strategies and practical, experiental utilization of those strategies.